Enamel Hypoplasia Management With Direct Composite Resin - Khairun Nisa; Hesti Witasari Jos Erry (Sriwijaya Journal of Dentistry, 2021)
Introduction: Disturbances during teeth growth and development may lead to dental abnormalities. Disruption in the process of formation of the enamel matrix may result in a surface defect known as enamel hypoplasia. Purpose: This case report aimed to show a technique of direct composite resin for esthetic resolution in anterior teeth with enamel hypoplasia. Case presentation: A 20-year-old male patient presented at the YARSI Dental Hospital (Jakarta) with a complaint of chalky white spots on the maxillary anterior teeth. The clinical examination showed wet white spots on the labial surfaces of 13, 21, and 23 (FDI), also caries on the labial and mesial surfaces of 12, 11, and 22. The treatment plan were composite resin direct veneers on After 5 months follow-up, evaluation of patients’s appearance showed that the affected teeth are maintained in good condition. Conclusion: Clinical success in the management of enamel hypoplasia depends on the severity of the lesion, the diagnosis, and the determination of a treatment plan.